PENGARUH VARIASI MENU DAN CITA RASA, PERSEPSI HARGA, KEBERSIHAN TERHADAP KEPUASAN KONSUMEN PADA RUMAH MAKAN DUTA MINANG JL. BRIGJEN KATAMSO - Felinda Astuti; Henny Welsa; Ignatius Soni Kurniawan (Universitas Sarjanawiyata Tamansiswa, 2019)
This research was conducted to examine the effect of menu variations and tastes, perceptions of price, cleanliness on customer satisfaction at Duta Minang Restaurant Jln. Brig. Gen. Katamso. This study uses the dependent variable namely menu variation and taste, price perception, cleanliness and independent variables, namely customer satisfaction. The sampling technique used is Simple Accidential Sampling. Simple Accidential Technique Sampling, which is known as opportunity sample or free sampling, was chosen because of comfortable accessibility and proximity to the researcher. Samples are only taken at consumers of Duta Minang Restaurant Jln. Brigadier General Katamso totaling 100 people. The procedure for collecting data uses questionnaires that are distributed to be filled by Duta Minang consumers. Data processing uses multiple regression analysis with SPSS 16.0 tools. Based on data analysis and the results of hypothesis testing in this study it can be concluded that menu variations and tastes have a positive effect on consumer satisfaction with a significance level of 0,000. Price perception has a positive effect on customer satisfaction with a significance level of 0,000. Cleanliness has a positive effect on consumer satisfaction with a significance level of 0.016. This gives the implication that companies with good hygiene can increase customer satisfaction. And simultaneously the variable variations in menu and taste, price perception, and cleanliness positively influence consumer satisfaction with the value of F obtained at 207,528 and an error rate of 5%, the ability of the regression equation in this study, to explain the magnitude of variation that occurs in the dependent variable of 86 , 2% while 13.8% is explained by variables that the researcher cannot explain.